Distributed Ledger Technology - Addressing the Challenges of Assurance in Accounting Systems: A Research Note - Kishore Singh; Amlan Haque; Sabi Kaphle; Janice Joowon Ban (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Background - With the progressive development of blockchain technology, its potential influence on the accounting and auditing professions is of interest to academia and practitioners. As the technology gains acceptance in businesses such as banking, stock exchanges, insurance, law, government services, and e-voting, business leaders are beginning to recognise its potential to transform their organisations. Despite concerns about how this technology will marginalise the accounting and auditing profession, blockchain continues to lag behind in adoption and there is time for accountants and auditors to reflect on their current practice and update their knowledge and skills to maintain their relevance to the industry. Motivation - The literature has not fully examined the implications of distributed ledger technology and its implications for the accounting and auditing profession. The intent of this research note is to identify opportunities for research that are of significance to the application of distributed ledger technology to accounting and auditing. Research Question - To identify possibilities that exist in researching the adoption, implementation and application of a distributed ledger solution in the context of accounting and auditing. Framework - Based on the literature, the study proposes a framework for a blockchain model of a simplified triple-entry bookkeeping system using smart contracts to automate self-verification and replication of transactions in a public distributed ledger. Findings - Drawing on the framework the article develops a series of research questions that may significantly reduce barriers and challenges facing organizations that want to implement blockchain technology in their accounting systems. Contribution - Given the complex nature of blockchain, cross disciplinary research is proposed to bring together information technology, accounting, assurance, economics and psychology resulting in further understanding of the technology as it relates to, and influences the accounting and auditing profession. In doing so, the paper makes several contributions to the literature.
Keywords: M15; M41; M42; O33; 650; Distributed ledger; blockchain; triple-entry bookkeeping; audit and assurance